2014
DOI: 10.1002/smj.2324
|View full text |Cite
|
Sign up to set email alerts
|

Unpaid crowd complementors: The platform network effect mirage

Abstract: Platforms have evolved beyond just being organized as multi‐sided markets with complementors selling to users. Complementors are often unpaid, working outside of a price system and driven by heterogeneous sources of motivation—which should affect how they respond to platform growth. Does reliance on network effects and strategies to attract large numbers of complementors remain advisable in such contexts? We test hypotheses related to these issues using data from 85 online multi‐player game platforms with unpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
172
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 303 publications
(174 citation statements)
references
References 83 publications
(128 reference statements)
2
172
0
Order By: Relevance
“…Following Gregoire et al (2009), we assume that a technology can exist independent from commercial outcomes. This means that our theory acknowledges that some complementors produce technologies for platform ecosystems without initially intending to profit from their technology (Boudreau & Jeppesen, 2015). Importantly, our definition of technology does not necessarily imply novelty.…”
Section: Mechanism Of Commercializationmentioning
confidence: 97%
See 4 more Smart Citations
“…Following Gregoire et al (2009), we assume that a technology can exist independent from commercial outcomes. This means that our theory acknowledges that some complementors produce technologies for platform ecosystems without initially intending to profit from their technology (Boudreau & Jeppesen, 2015). Importantly, our definition of technology does not necessarily imply novelty.…”
Section: Mechanism Of Commercializationmentioning
confidence: 97%
“…Interestingly, he also found that adding developers within a particular software genre tended to be associated with lower rates of new versions of existing titles being generated, or a "crowding out" of innovation incentives (Boudreau, 2012). In related platform ecosystem work, Boudreau and Jeppesen (2015) studied development rates of full-conversion modifications ("mods") built on online multiplayer first-person shooter game platforms. These development rates existed in the absence of financial incentives because the mod complementors were restricted by license from charging users.…”
Section: Scholars Have Noted That Platform Owners Can Employ Various mentioning
confidence: 99%
See 3 more Smart Citations